The Universe next door. The making of Tommrrow's Science. - Marcus Chown (Oxford University Press, 2002)
The idea that an atom can be in two places at once defies logic. Yet this is now an established scientific fact. In The Universe Next Door, science writer Marcus Chown examines a dozen mind-bending new ideas that also fly in the face of reason--but that, according to eminent scientists, might just be crazy enough to be true. Could time run backwards? Is there a fifth dimension? Does quantum theory promise immortality? To explore these questions, Chown has interviewed some of the most imaginative and courageous people working at the forefront of science, and he has come away with a smorgasbord of mind-expanding ideas. For instance, Lawrence Schulman at New York's Clarkson University believes there could be regions in our Universe where stars unexplode, eggs unbreak and living things grow younger with every passing second. Max Tegmark, at the University of Pennsylvania, believes there could be an infinity of realities stacked together like the pages of a never-ending book (with an infinite number of versions of you, living out an infinite number of different lives). And David Stevenson of Cal Tech argues that life may exist on worlds drifting in the cold, dark abyss between the stars, worlds without suns to warm them. Indeed, these worlds may be the most common sites for life in the universe. Was our universe created by super-intelligent beings from another universe? Is there evidence of extraterrestrial life lying right beneath our feet? The Universe Next Door ponders these and many other thought-provoking questions. You may not agree with all the answers but your head will be spinning by the time you reach the last page.